2007
DOI: 10.1093/brain/awm269
|View full text |Cite
|
Sign up to set email alerts
|

McLeod myopathy revisited: more neurogenic and less benign

Abstract: The X-linked McLeod neuroacanthocytosis syndrome (MLS) has originally been denoted as 'benign' McLeod myopathy. We assessed the clinical findings and the muscle pathology in the eponymous index patient, Hugh McLeod, and in nine additional MLS patients. Only one patient had manifested with neuromuscular symptoms. During a mean follow-up of 15 years, however, eight patients including the initial index patient showed elevated skeletal muscle creatine kinase levels ranging from 300 to 3000 U/L, and had developed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
56
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 31 publications
3
56
0
1
Order By: Relevance
“…Les complications ou manifestations neuromusculaires n'y sont pas rares et peuvent prendre plusieurs formes : neuropathie sensitivomotrice, ou plus souvent atteinte myopathique de sévérité variable allant d'une simple hyperCKémie, (avec, il faut le souligner, un risque non négligeable de rhabdomyolyse), jusqu'à des tableaux exceptionnellement déficitaires. Une cardiomyopathie a également été rapportée à plusieurs reprises dans la litté-rature, généralement après la cinquantaine [5,6,8]. McLeod mais ceci n'a jamais pu être formellement démontré [9].…”
Section: Discussionunclassified
“…Les complications ou manifestations neuromusculaires n'y sont pas rares et peuvent prendre plusieurs formes : neuropathie sensitivomotrice, ou plus souvent atteinte myopathique de sévérité variable allant d'une simple hyperCKémie, (avec, il faut le souligner, un risque non négligeable de rhabdomyolyse), jusqu'à des tableaux exceptionnellement déficitaires. Une cardiomyopathie a également été rapportée à plusieurs reprises dans la litté-rature, généralement après la cinquantaine [5,6,8]. McLeod mais ceci n'a jamais pu être formellement démontré [9].…”
Section: Discussionunclassified
“…The patients have elevated creatinine kinase levels and axonal neuropathy. The neuromuscular involvement in choreoacanthocytosis includes myopathy and axonal sensorymotor neuropathy [5]. McLeod syndrome should be considered as a differential diagnosis of choreoacanthocytosis as neuromuscular involvement is more common in this subtype of neuroacanthocytosis [6].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, it has been shown that only 40% of the patients exhibit non-specific myopathic changes on muscle biopsy, whereas 100% exhibit neurogenic changes due to axonal neuropathy [2]. Which was the cause of CKelevation in the presented patients?…”
mentioning
confidence: 92%
“…Only two of six patients (33%) developed weakness or wasting, despite a mean age of 45 years. In a recent study on 10 patients, however, 80% developed weakness and wasting within a mean observational period of 15 years [2]. How to explain this discrepancy?…”
mentioning
confidence: 97%
See 1 more Smart Citation